Golden in death [compact disc, unabridged] - Robb, J. D., 1950- (Robb, J. D., 1950- In death novel., 2020)
A pediatrician receives poison in the mail, and Detective Eve Dallas must find the sender. But when someone else dies, Eve knows she's dealing with a madman, or someone with a secret connection.